Monetary Issues in the Middle East and North Africa Region : A Policy Implementation Handbook for Central Bankers - Gray, Simon (Departmental Papers; Departmental Paper ;, 2013)
This paper documents the main themes covered in two seminars (December 2011 and September 2012) on monetary policy and implementation at the IMF-Middle East Center for Economics and Finance, and includes country case studies. Against the backdrop of the global financial crisis and swings in cross-border capital flows, operational frameworks have become more flexible, and liquidity management has impacted the relationship between the policy rate corridor and market rates. The balance sheet structure of central banks in the Middle East and North Africa (MENA) shows differences between oil exporters and others, while a few countries have exhibited notable changes since early 2011. Collateral now has a significant financial stability function. Although only one MENA country is part of the G20, implementation of the Basel III bank capital adequacy and liquidity rules will most likely impact banks' way of doing business in MENA countries, even if indirectly.